Stochastic voltage stability margin in unbalance feeder with fuzzy based distributed generation placement - Prasad Sharma, Jagdish; Ravishankar Kamath, H (International Journal of Engineering and Technology, 2018)
In this paper, the impact of distributed generation (DG) integration on worst stochastic voltage stability margin is investigated for a modified IEEE 37 node test system. This unbalance test system has voltage sensitive load model for industrial, commercial and residential consumers and load flow computed in MATLAB environment with 15 minutes metering time interval for a whole day. DG integration is based on fuzzy expert system and integrated between 35 to 73 period of metering time interval. The stochastic voltage stability margin for all phase are evaluated under three different DG operational scenarios and compared with results obtained in the base case. The cause and consequence of unbalance phenomena is also broadly discussed in detail.Â